Pelatihan Dalam Pengaplikasian Konsep Transformasi Geometri Pada Desain Motif Batik di SMP Negeri 81 Jakarta - Wahidin Wahidin; Fitri Alyani (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2022)
Mathematics is learned and developed to solve daily problems. One of the obstacles of students interesnt in mathematics is the lack of information related to the application of mathematics in daily life that is conveyed to students. In fact, the mathematics material learned in school is an early concept that is widely used in everyday life. One of them is the transformation of the geometry. Geometry Transformation is a branch of mathematics in the algebra. The use of geometric concepts is often found in everyday life. Based on these problems, the community service team offered a solution in the form of training in the concept of geometric transformation with batik motif designs. Keywords: Transformation geometry, batik motif design.